Special Issue “Role of Exercises in Musculoskeletal Disorders—4th Edition” - Giuseppe Musumeci (Journal of Functional Morphology and Kinesiology)
This fourth edition of the Special Issue titled “Role of Exercises in Musculoskeletal Disorders” significantly enriches the discourse on the effectiveness and feasibility of physical activity in managing patients with musculoskeletal disorders [...]